Prognosis conversations in advanced liver disease: A qualitative interview study with health professionals and patients. - Jennifer Arney; Caroline Gray; Jack A Clark; Donna Smith; Annie Swank; Daniel D Matlock; Jennifer Melcher; Fasiha Kanwal; Aanand D Naik (PLoS ONE, 2022)
Advanced Liver Disease (AdvLD) is common, morbid, and associated with high likelihood of death. Patients may not fully understand their prognosis and are often unprepared for the course of illness. Little is known about how and when to deliver prognosis-related information to patients with AdvLD, who should participate, and what should be discussed. We conducted in-depth interviews with a multi-profession sample of Hepatology clinicians and patients with AdvLD. Participants were drawn from three geographically diverse facilities (New England, Texas, California). We used inductive and deductive qualitative data analysis approaches to identify themes related to AdvLD prognosis discussions. Thematic analysis focused on content, timing, and participants' roles in prognosis discussions. In total, 31 patients with AdvLD and 26 multi-profession clinicians completed interviews. Most participants provided a broad conceptualization of prognosis beyond predictions of survival, including expectations about illness course, ways to manage or avoid complications and a need to address patients' emotions. Patients favored initiating discussions early in the AdvLD course and welcomed a multi-profession approach to conducting discussions. Clinicians favored a larger role for specialty physicians. All participants recognized that AdvLD prognosis discussions occur infrequently and favored a structured, standardized approach to broadly discussing prognosis. Patients with AdvLD and their clinicians favored a multifaceted approach to prognosis conversations including discussions of life expectancy, predictions about likely course of liver disease, and expected changes in function and capabilities over time. Structured and early prognosis discussions should be part of routine AdvLD care.